COMPARISON OF RATE OF RETRACTION OF CANINE ON ROUND AND RECTANGULAR WIRES - Hamid, Fatima; Bangash, Azhar Ali; Saeed, Munazza; Tariq, Sana; Khan, Mehwish (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the mean rate of canine retraction on round and rectangular stainless steel arch wires. Study Design: Quasi experimental study. Place and Duration of Study: Orthodontics department, Armed Forces Institute of Dentistry, Rawalpindi, from May 2017to Jul 2018. Methodology: Forty patients were inducted requiring fixed orthodontic therapy with first premolar extractions. After initial alignment and premolar extractions, canine retraction was initiated on customized arch wires having a round wire segment on one side and a rectangular wire segment on another. The distance between lateral incisor and canine were measured before starting retraction and 1-month post. Difference between the two measurements was recorded and data was analyzed using IBM SPSS 21.0 and paired sample t-test was applied. Results: Forty patients (80 teeth) with 21 males (52.5%) and 19 females (47.5%) were included. The mean rate of maxillary tooth movement observed on the experimental side was 0.51 ± 0.1549 mm over a period of one month. Whereas, on the control side 0.20 ± 0.1086 mm movement was recorded. There was a difference of 0.31 ± 0.2036 mm per month in the rate of space closure between the two sides (p=0.01). Conclusion: Mean rate of canine retraction was significantly greater in round wire segment as compared to the rectangular wire segment.